Analysis of the Impact of Monopoly Practices in the Entertainment Sector - Kartiko, Nafis Dwi; Soegiono, Samuel Putra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the practice of monopoly in the entertainment sector in Indonesia. Specifically, it focuses on the alleged conspiracy between venue owners and sound system equipment rental vendors. This study investigates the extent to which exclusive cooperation can be categorized as a monopoly according to Law No. 5/1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, using the Normative-Dogmatic Juridical method. The text also mentions the prohibition of monopolistic practices and unfair business competition. The focus is on analyzing analysis of existing legal norms, through a deductive approach to identify violations of the law that occur without connecting directly with the social context of society. Research Results: The study indicates that conspiracies in the entertainment industry reflect monopolistic practices that violate legal norms. These practices eliminate market diversity, limit consumer choice, and result in uncompetitive prices and reduced service quality. These findings contribute to the competition law literature by providing a new interpretation of monopolistic practices at a smaller scale and in a more contextualized manner. They also offer input for stakeholders in designing effective regulations to prevent monopolization, support innovation, and protect consumers.